Public health and military health. (21st November 2022) - Falconer Hall, Thomas; Bricknell, MCM; Ross, DA
Abstract: This paper summarizes the role of Public Health specialists within the UK Defence Medical Services (DMS). The armed forces have a need for expert advice on health improvement, health protection and healthcare public health. The first professor of military hygiene, Dr Edmund Parkes, was a leading pioneer in the public health movement of the late 19th century. Since then, the armed forces have evolved the term 'hygiene', though 'health', to 'well-being'. Military doctors with an interest in medical administration and the health of populations have longstanding links with their civilian peers, through the Society of Medical Officers of Health and its successor the Faculty of Public Health. The specialty of Public Health in the armed forces is multidisciplinary, following the same educational pathway as civilian peers. The speciality has made important contributions during global health emergencies including the Ebola outbreak in 2014 and the recent COVID-19 pandemic. Although a small cadre, within the DMS and in the UK Public Health workforce, they have an important role in keeping our armed forces ready for operations. We celebrate the 50th anniversary of the Faculty of Public Health and expect that the DMS will contribute to the further development of the specialty.